Transposable elements in Coffea (Gentianales : Rubiacea) transcripts and their role in the origin of protein diversity in flowering plants - Lopes, Fabricio Ramon [UNESP]; Carazzolle, Marcelo Falsarella; Guimaraes Pereira, Goncalo Amarante; Colombo, Carlos Augusto; Aparecida Carareto, Claudia Marcia [UNESP] (Springer Heidelberg, 2008)
Transposable elements are major components of plant genomes and they influence their evolution, acting as recombination hot spots, acquiring specific cell functions or becoming part of protein-coding regions. The latter is the subject of the present analysis. This study is a report on the annotation of transposable elements (TEs) in expressed sequences of Coffea arabica, Coffea canephora and Coffea racemosa, showing the occurrence of 383 ESTs and 142 unigenes with TE fragments in these three Coffea species. Based on selected unigenes, it was possible to suggest 26 putative proteins with TE-cassette insertions, demonstrating a likely contribution to protein variability. The genes for two of those proteins, the fertility restorer (FR) and the pyrophosphate-dependent phosphofructokinase (PPi-PFKs) genes, were selected for evaluating the impact of TE-cassettes on host gene evolution of other plant genomes (Arabidopsis thaliana, Oryza sativa and populus trichocarpa). This survey allowed identifying a FR gene in O. sativa harboring multiple insertions of LTR retrotransposons that originated new exons, which however does not necessarily mean a case of molecular domestication. A possible transduction event of a fragment of the PPi-PFK beta-subunit gene mediated by Helitron ATREPX1 in Arabidopsis thaliana was also highlighted.
Keywords: Transposable element; Coffea genome; protein diversity; molecular domestication; gene transduction